2018
DOI: 10.1111/mec.14504
|View full text |Cite
|
Sign up to set email alerts
|

Integrating genomic and phenotypic data to evaluate alternative phylogenetic and species delimitation hypotheses in a recent evolutionary radiation of grasshoppers

Abstract: Although resolving phylogenetic relationships and establishing species limits are primary goals of systematics, these tasks remain challenging at both conceptual and analytical levels. Here, we integrated genomic and phenotypic data and employed a comprehensive suite of coalescent-based analyses to develop and evaluate competing phylogenetic and species delimitation hypotheses in a recent evolutionary radiation of grasshoppers (Chorthippus binotatus group) composed of two species and eight putative subspecies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 123 publications
3
68
0
Order By: Relevance
“…Thus, incorporating morphological traits has no or very little influence on the outcome of ibpp analyses and the impact of phenotypic traits seems to be overridden by the high amount of genetic data. Our analyses suggest that the species delimitation approach implemented in ibpp does not really help to reduce the number of delineated species, indicating that integrating phenotypic and genetic data into this framework cannot prevent species overestimation (Noguerales et al, ; Sukumaran & Knowles, ). In sum, the strong genetic structure in our study system and the high number of loci employed are likely to have extraordinarily inflated the number of species identified by bpp and bfd * and integrative analyses implemented in ibpp does not seem to help to ameliorate this problem.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Thus, incorporating morphological traits has no or very little influence on the outcome of ibpp analyses and the impact of phenotypic traits seems to be overridden by the high amount of genetic data. Our analyses suggest that the species delimitation approach implemented in ibpp does not really help to reduce the number of delineated species, indicating that integrating phenotypic and genetic data into this framework cannot prevent species overestimation (Noguerales et al, ; Sukumaran & Knowles, ). In sum, the strong genetic structure in our study system and the high number of loci employed are likely to have extraordinarily inflated the number of species identified by bpp and bfd * and integrative analyses implemented in ibpp does not seem to help to ameliorate this problem.…”
Section: Discussionmentioning
confidence: 89%
“…Recent empirical and theoretical studies have shown the limitations of Bayesian species delimitation approaches based on the multi-species coalescent (MSC) model (Rannala & Yang, 2013;Yang & Rannala, 2010), pointing out that such methods are not able to statistically distinguish genetic structure due to population isolation from true species boundaries and tend to over-split genetically differentiated populations rather than capturing species divergence (Huang, 2018;Leaché et al, 2018;Leaché, Zhu, Rannala, & Yang, 2019;Sukumaran & Knowles, 2017). The problem of species overestimation can be particularly exacerbated when using vast genome-wide data due to the high power of a large number of markers (hundreds to tens of thousands) to detect fine-grain population structure (Hime et al, 2016;Noguerales et al, 2018;Sukumaran & Knowles, 2017). In this line, recent empirical studies have found that geographically continuous intraspecific populations presenting genotypic differences simply resulted from isolation by distance can be delimited as distinct species when using hundreds of loci (Huang, 2018; Pyron, Hsieh, Lemmon, Lemmon, & Hendry, 2016).…”
Section: Integrative Species Delimitationmentioning
confidence: 99%
See 2 more Smart Citations
“…The three species recognized under this model are Phrynosoma blainvillii , Phrynosoma cerroense and P. coronatum , with geographic distributions in northern Baja California and California, central Baja California (including Cedros Island) and southern Baja California, respectively (Figure ). There is a general consensus among biologists that an integrative approach that combines diverse types of data from ecology, morphology and genetics will help increase taxonomic accuracy (Dayrat, ; Noguerales et al., ; Solís‐Lemus, Knowles, & Ané, ).…”
Section: Discussionmentioning
confidence: 99%